A LIMITED-MEMORY QUASI-NEWTON INVERSION FOR 1D MAGNETOTELLURICS - Avdeeva A.; Avdeev D. (My University, 2006)
We apply a limited-memory quasi-Newton (QN) method to the 1D magnetotelluric (MT) inverse problem. Using this method we invert a realistic synthetic MT impedance data set calculated for a layered earth model. The calculation of gradients based on the adjoint method speeds up the inverse problem solution many times. In addition, regularization stabilizes the QN inversion result and a few correction pairs are sufficient to produce reasonable results. Comparison with the L-BFGS-B algorithm shows similar convergence rates. This study is a first step towards the solution of large-scale electromagnetic problems, with a full treatment of the 3D conductivity structure of the earth. © 2006 Society of Exploration Geophysicists.
Keywords: GEOMAGNETISM; GEOPHYSICS COMPUTING; INVERSE PROBLEMS; TERRESTRIAL ELECTRICITY